The human geographies of coastal sustainability transitions - Axon, Stephen (Towards coastal resilience and sustainability, 2018)
This chapter provides an overview of public engagement, its importance and effective approaches to meaningfully involve the public with coastal sustainability transitions. It presents two case studies, Guernsey, British Channel Islands and Cape Wind, Massachusetts. These illustrate how concepts of identity, marginality and engagement are essential to the development of coastal sustainability transitions. As the case study of Guernsey outlines, coastal sustainability transition-related public engagement should seek to enhance the local distinctiveness of coastal areas and 'fit within the wider narrative of place identity and how individuals feel attached to places that are ascribed with specific meanings'. Furthermore, as the case study of Cape Wind illustrates, coastal sustainability transitions need to connect with local communities in terms of addressing immediate social and economic concerns. Therefore, as a research agenda, the human geographies of coastal sustainability transitions can be of substantial value to the practical application of sustainability. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Case-studies; Coastal sustainability; Economic concerns; Effective approaches; Local community; Massachusetts; Public engagement; Research agenda; Sustainable development; dept.egm